Mapping and Remote Sensing Technology for Agricultural Land Management in China - Shi Yonglong; Chu Qingjun; Benxiang Guanghui (Yayasan Adra Karima Hubbi, 2024)
Agricultural land management in China faces significant challenges due to rapid urbanization, climate change, and the need for sustainable practices. Advanced technologies such as mapping and remote sensing offer promising solutions to enhance agricultural productivity and sustainability. These technologies provide precise data for monitoring crop health, soil conditions, and land use, enabling better decision-making and resource management. This study aims to evaluate the effectiveness of mapping and remote sensing technology in improving agricultural land management in China. The research assesses how these technologies can enhance crop monitoring, optimize resource use, and support sustainable farming practices. A mixed-methods approach was employed, combining quantitative data from satellite imagery and field surveys with qualitative insights from interviews with farmers and agricultural experts. Satellite imagery was analyzed to monitor crop health, soil moisture, and land use patterns. Field surveys were conducted to validate the remote sensing data. Interviews with farmers and experts provided additional insights into these technologies' practical benefits and challenges. The findings indicate that mapping and remote sensing technology significantly improve agricultural land management. Crop health monitoring through remote sensing showed a 25% increase in accuracy compared to traditional methods. Optimized resource use was observed, with a 20% reduction in water and fertilizer usage. Land use patterns were more efficiently managed, leading to better crop rotation and soil conservation practices. Farmers reported enhanced decision-making capabilities and improved crop yields. Mapping and remote sensing technology substantially benefit agricultural land management in China. The increased accuracy in crop monitoring and optimized resource use contribute to higher productivity and sustainability. Further research and investment in these technologies are recommended to maximize their potential and support sustainable agricultural practices.